1998
DOI: 10.1111/j.2044-8325.1998.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Active coping and need for control as moderators of the job demand–control model: Effects on burnout

Abstract: Empirical research on Karasek's job demand–control (JD‐C) model has often failed to demonstrate the predicted interaction effect of high job demands and low job control on measures of strain. It has been suggested that the conceptualization of the control dimension as well as the neglect of workers' individual characteristics in the JD‐C model may be responsible for its relative lack of empirical support. In the current study among 367 Dutch nurses from 18 intensive care units, a more focused measure of contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
201
4
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(241 citation statements)
references
References 32 publications
20
201
4
8
Order By: Relevance
“…Investigators such as Parker andSprigg (1999) andDe Rijk et al (1998) have already shown that it is possible to produce more carefully detailed reports of the influence of job characteristics if account is taken of personal characteristics. Consequently, we will include the personal characteristic of a self-directed learning orientation.…”
Section: Criticism Of the Dcs Modelmentioning
confidence: 99%
“…Investigators such as Parker andSprigg (1999) andDe Rijk et al (1998) have already shown that it is possible to produce more carefully detailed reports of the influence of job characteristics if account is taken of personal characteristics. Consequently, we will include the personal characteristic of a self-directed learning orientation.…”
Section: Criticism Of the Dcs Modelmentioning
confidence: 99%
“…Rather than moderating the negative effects of heavy workloads, job control itself becomes a source of stress. By contrast, if individual's personality is characterised by a highly active approach to coping with stressful situations, a high degree of job control moderates the negative effects of heavy workloads (de Rijk et al, 1998;Van der Doef and Maes, 1999;Sparks et al, 2001).…”
Section: Control and Discretionmentioning
confidence: 98%
“…Indeed, samples of nurses have been used in tests of both the JDC and JDC-S models (Bourbonnais et al 1999;de Rijk et al, 1998;Fox et al, 1993;Ganster et al, 2001;Morgan, Semchuk, Stewart & D"Arcy, 2002;Laschinger, Finegan & Shamian, 2001;Tummers et al, 2001). The nursing profession has been found to fall into the "active job" quadrant of the model, characterized by high demands and high control, in international surveys (Karasek & Theorell, 1990) and in a direct test of the model within the nursing profession (Seago, 1996;Seago & Faucett, 1997), although one sample found that nurses in rural nursing homes had high control and low demands, classifying the job as low strain (Morgan et al).…”
Section: Applicability To Nursingmentioning
confidence: 99%
“…The model has also predicted health care costs incurred by the sample of nurses, although it did not predict mental health as measured by distress and well-being (Ganster et al, 2001). Additionally, an expanded model that included active coping predicted burnout among nurses (de Rijk et al, 1998).…”
Section: Applicability To Nursingmentioning
confidence: 99%